IMPLEMENTASI LANDASAN PENDIDIKAN DALAM MENGOPTIMALKAN PERAN GURU DAN MANAJEMEN SEKOLAH DALAM MENCEGAH PERILAKU BULLYING - Karim, Ajerin; Aunurrahman, Aunurrahman; Halida, Halida; Ratnawati, RR Eka (Academy of Education Journal, 2023)
The importance of an educational foundation in overcoming the problem of bullying in the entire learning process is the main key to creating a safe and comfortable school environment. The role of teachers and school management is very important in preventing bullying at school. This research aims to explain the implementation of educational foundations in optimizing the role of teachers and school management in preventing bullying behavior. By using a literature review approach, reviewing literature sources, especially journals, books and other sources that support research. This research method uses qualitative research to understand and explain phenomena and events in a broader social and cultural context. The research results show that the role of teachers and school management can help overcoming the problem of bullying by building cooperation and responsibility with all school components, including parents and other related parties, thereby creating a safe and inclusive school environment. It is hoped that this research can help teachers and school management in overcoming the problem of bullying.